Absence of Progressive Bone Loss Following Peri-Implantitis Surgical Therapy with Implantoplasty: A Case Series - Arthur Brincat; Angéline Antezack; Camille Sadowski; Mathias Faure-Brac; Romain Ohanessian; Virginie Monnet-Corti (Applied Sciences, 2023)
Background: Peri-implantitis, a bacteria-associated inflammatory disease, is characterized by inflammation of the peri-implant mucosa and progressive loss of the supporting bone, thereby reducing the chances of dental implant survival. The absence of progressive marginal bone loss is crucial for implant success. The aim of this study is to assess the peri-implantitis resolution by measuring the absence of progressive bone loss rate around the implant over a period of one year to more than three years after surgical reconstructive (REC) treatment, apically repositioned flap (ARP) surgery, or combined (COM) treatment of peri-implantitis with implantoplasty. Methods: Peri-implantitis patients, that underwent surgical therapy with implantoplasty and that enrolled in a regular peri-implant supportive care program with a follow up of ≥12 months, were recruited in this study. ARP, REC, or COM surgical therapy was performed depending on the anatomy of the bone defect. For REC and COM groups, intraosseous defects were filled with a bone substitute. The ARP group consisted of an apically positioned flap without osseous surgery. Absence of progressive marginal bone loss was evaluated on radiographs of the treated implants. Results: A total of 57 patients (91 implants) were included. The study occurred over a follow-up period of 12 to 42 months (mean = 24 months). The surgical treatment with implantoplasty yielded an absence of progressive bone loss rate of 96.7% at implant level (100% REC, 98% COM, 92.9% ARP) and 96.5% at patient level. Three implants had to be removed in two patients due to relapse or progression of peri-implantitis. Conclusions: This case series demonstrated that implantoplasty during surgical treatment of peri-implantitis lesions resulted in favorable biological conditions to maintain functional implants with 96.7% of implants that did not show bone loss over time from one year to more than three years.